Concurrent Targeting of KRAS and AKT by MiR-4689 Is a Novel Treatment Against Mutant KRAS Colorectal Cancer - Masayuki Hiraki; Junichi Nishimura; Hidekazu Takahashi; Xin Wu; Yusuke Takahashi; Masaaki Miyo; Naohiro Nishida; Mamoru Uemura; Taishi Hata; Ichiro Takemasa; Tsunekazu Mizushima; Jae-Won Soh; et al. (Elsevier, 2015)
KRAS mutations are a major cause of drug resistance to molecular-targeted therapies. Aberrant epidermal growth factor receptor (EGFR) signaling may cause dysregulation of microRNA (miRNA) and gene regulatory networks, which leads to cancer initiation and progression. To address the functional relevance of miRNAs in mutant KRAS cancers, we transfected exogenous KRASG12V into human embryonic kidney 293 and MRC5 cells with wild-type KRAS and BRAF genes, and we comprehensively profiled the dysregulated miRNAs. The result showed that mature miRNA oligonucleotide (miR)-4689, one of the significantly down-regulated miRNAs in KRASG12V overexpressed cells, was found to exhibit a potent growth-inhibitory and proapoptotic effect both in vitro and in vivo. miR-4689 expression was significantly down-regulated in cancer tissues compared to normal mucosa, and it was particularly decreased in mutant KRAS CRC tissues. miR-4689 directly targets v-ki-ras2 kirsten rat sarcoma viral oncogene homolog (KRAS) and v-akt murine thymoma viral oncogene homolog 1(AKT1), key components of two major branches in EGFR pathway, suggesting KRAS overdrives this signaling pathway through inhibition of miR-4689. Overall, this study provided additional evidence that mutant KRAS functions as a broad regulator of the EGFR signaling cascade by inhibiting miR-4689, which negatively regulates both RAS/mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K)/AKT pathways. These activities indicated that miR-4689 may be a promising therapeutic agent in mutant KRAS CRC.